Emergency Physicians' Workstation Design: An Observational Study of Interruptions and Perception of Collaboration During Shift-End Handoffs. (October 2021) - Joshi, Rutali; Joseph, Anjali; Ossmann, Michelle; Taaffe, Kevin; Pirrallo, Ronald; Allison, David; Perino, Larissa Coldebella
Background: Frequent external interruptions and lack of collaboration among team members are known to be common barriers in end-of-shift handoffs between physicians in the emergency department. In spite of being the primary location for this crucial and cognitively demanding task, workstations are not designed to limit barriers and support handoffs. Objective: The purpose of this study is to examine handoff characteristics, actual and perceived interruptions, and perceived collaboration among emergency physicians performing end-of-shift handoffs in physician workstations with varying levels of enclosures—(a) open-plan workstation, (b) enclosed workstation, and (c) semi-open workstation. Method: Handoff and interruption characteristics were captured through in-person observations of 60 handoffs using an iPad-based tool. Additionally, physicians participating in the handoffs responded to a survey pertaining to their perception of interruptions and collaboration with clinicians during each phase. Other organizational and demographic data were obtained from the hospital database, surveys, and observations. Results: Physicians working in the open workstation experienced a significantly higher number of interruptions/hour (18.08 int/hr) as compared to the semi-open (13.62 int/hr) and enclosed workstations (11.41 int/hr). Most physicians perceived that they were interrupted in the semi-open and open workstations. In addition, majority of physicians in the enclosed pod perceived high collaboration with clinicians involved in and present in the workstation during handoff. Conclusion: This correlational study showed positive outcomes experienced by physician working in the enclosed workstation as compared to the open and semi-open workstations.